A Study on Watermelon (Citrullus Lanatus) Juice Preserved with Chemical Preservatives at Refrigeration Temperature - Alam, MK; Hoque, MM; Morshed, S; Shahriar, SMS; Begum, A (Journal of Environmental Science and Natural Resources, 2013)
This study was done to analyse the effect of chemical preservatives on watermelon juice. The samples were; pasteurized watermelon juice (T1), pasteurized watermelon juice +20% sucrose (T2), pasteurized watermelon juice +0.1% sodium benzoate (T3), pasteurized watermelon juice +20% sucrose +0.1% sodium benzoate (T4), pasteurized watermelon juice +0.1% potassium sorbate (T5), pasteurized watermelon juice +20% sucrose+0.1% potassium sorbate (T6), pasteurized watermelon juice +0.05% sodium benzoate +0.05% potassium sorbate (T7), pasteurized watermelon juice +20% sucrose +0.05% sodium benzoate +0.05% potassium sorbate (T8), pasteurized watermelon juice +0.1% sodium benzoate +0.1% potassium sorbate (T9), pasteurized watermelon juice +20% sucrose +0.1% sodium benzoate +0.1% potassium sorbate (T10). The samples were stored at 4 - 15°C for three months. T1 and T2 were rejected soon due to spoilage. Minimum ascorbic acid content was reduced in T10 (23.85%), while maximum in T4 (44.44%). Minimum acidity was increased in T10 (50.00%), while maximum in T1 (107.69%). Treatments T10, T9 T8 and T6 were found most acceptable in maintaining the sensory characteristics compared to others during storage. Among all the treated juice sample T10 was most effective in maintaining the sensory and nutritional quality during storage. DOI: http://dx.doi.org/10.3329/jesnr.v5i2.14597 J. Environ. Sci. & Natural Resources, 5(2): 23-28 2012